Perencanaan Water Cushion Berbasis Tekanan Hidrostatik pada Operasi Tubing Conveyed Perforating: Studi Kasus Sumur UWL-001 - Kamid, Abdul; Winarto Winarto; Yudiantoro, Ismanu; Firdaus, Miftahul (Lembaga Pengembangan Kinerja Dosen, 2026)
UWL-001 is an exploration well located in the Banggai area, Central Sulawesi, where the completion program applies Tubing Conveyed Perforating (TCP) with an underbalance perforation approach. In this method, the hydrostatic pressure inside the wellbore must remain lower than the reservoir pressure; therefore, an appropriate water cushion design is required to satisfy the minimum pressure requirement of the Mechanical Safety Impact (MSI) firing head while maintaining the underbalance condition. This study aims to evaluate the water cushion design for the TCP operation in UWL-001 using a hydrostatic pressure approach. A descriptive quantitative case study was conducted using operational data provided by PT Elnusa Tbk, including well data, Drill Stem Test (DST) string configuration, log correlation results, reservoir pressure, and the water cushion program. Hydrostatic pressure calculations were employed to determine the optimum water cushion height, hydrostatic pressure, underbalance pressure, the number of tubing joints filled with water, and the required fluid volume. The initial design resulted in a water cushion height of 192 m, requiring 22 tubing joints and 5.8 bbl of water. During field implementation, the operator increased the water cushion height to 368 m, producing a hydrostatic pressure of 523 psi, an underbalance pressure of 2010 psi, 41 tubing joints, and 10.5 bbl of water. Although the hydrostatic pressure increased, the underbalance condition was successfully maintained because the hydrostatic pressure remained below the reservoir pressure. These findings demonstrate that the hydrostatic pressure approach provides an effective basis for designing a water cushion capable of ensuring reliable firing head activation while preserving the underbalance condition during Tubing Conveyed Perforating operations